Honorary authorship in biomedical journals: how common is it and why does it exist? - Al-Herz, Waleed (Journal of medical ethics, 2014)
Background The number of coauthors in the medical literature has increased over the past 50 years as authorship continues to have important academic, social and financial implications. Aim and method The study aim was to determine the prevalence of honorary authorship in biomedical publications and identify the factors that lead to its existence. An email with a survey link was sent anonymously to 9283 corresponding authors of PubMed articles published within 1 year of contact. Results A completed survey was obtained from 1246 corresponding authors, a response rate of 15.75%. One-third (33.4%) admitted that they had added authors who did not deserve authorship credit. Origin of the study from Europe and Asia (p ≤ 0.001 and 0.005, respectively), study type as case report/case series (p=0.036) and increasing number of coauthors were found to be the associated factors on multivariate analysis. Journal impact factor was also found to be associated with honorary authorship (mean journal impact factor was 4.82 (SD 6.32) for those who self-reported honorary authorship and 5.60 (SD 7.13) for those who did not report unjust authorship, p=0.05). In retrospect, 75% of the authors indicated that they would remove unjustified names from the authorship list. Reasons for adding honorary authors were complimentary (39.4%), to avoid conflict at work (16.1%), to facilitate article acceptance (7.2%), and other (3.6%). Conclusions Honorary authorship is relatively common in biomedical publications. Researchers should comply with the International Committee of Medical Journal Editors’ criteria for authorship.